2005
DOI: 10.1007/s00299-004-0905-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed transcripts from planthopper-infested wild rice (Oryza minuta)

Abstract: A subtracted library was constructed from planthopper-infested wild rice (Oryza minuta) by suppression subtractive hybridization in combination with mirror orientation selection. To screen the differentially expressed transcripts in the library, we applied a cDNA microarray containing 960 random clones in a reverse Northern blot analysis using cDNA probes prepared from the mRNAs of control and planthopper-infested samples. On the basis of the signal intensities and expression ratios obtained from experiments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Similar patterns of results have been observed in incompatible interactions between rice plants and the brown planthopper, Nilaparvata lugens Stahl, (Cho et al, 2005) and between wheat plants and the Hessian fly, Mayetiola destructor (Harris) (Zhu et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Similar patterns of results have been observed in incompatible interactions between rice plants and the brown planthopper, Nilaparvata lugens Stahl, (Cho et al, 2005) and between wheat plants and the Hessian fly, Mayetiola destructor (Harris) (Zhu et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…The feeding of brown plant hoppers on rice up-regulates several genes involved in phenylpropanoid biosynthesis and genes required for sesquiterpene synthesis (Zhang et al 2004;Cho et al 2005). In tomato, aphid infestation up-regulates SA signaling while in Arabidopsis SA has been shown to have a neutral and negative effect on aphid and silver leaf whitefly growth, respectively (Pegadaraju et al 2005;Zarate et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the BPH causes mechanical wounding by chewing, but it does not kill the host cells as a biotrophic insect (Sogawa, 1976;Kim and Sohn, 2005). In an earlier study, we screened O. minuta transcriptomes from wound-, BPH-, or rice blasttreated leaves and normal conditioned leaves in a high-throughput system to identify useful defenserelated genes from O. minuta (Cho et al, 2004a(Cho et al, , 2004b(Cho et al, , 2005Shim et al, 2004). In the study reported here, we identified a novel gene induced by wound-, BPH-, and M. oryzae in O. minuta.…”
mentioning
confidence: 89%
“…At least 10 larvae of the BPH (Nilaparvata lugens) Korean biotype1 were placed on each plant (Cho et al, 2005). For the wound treatment, the entire leaf area was punctured, except for the main vein, using needles.…”
Section: Pathogen Inoculationmentioning
confidence: 99%